How does the use of ICT in the classroom influence the way teachers act? - Dias, R.; Oliveira, A.; Cruz, M. (Proceedings of the 20th Iberian Conference on Information Systems and Technologies (CISTI 2025) – Iberian Proceedings of CISTI 2025, 2025)
As society evolves, the use of (new) technologies has ac- companied and contributed to this development. Many of these technologies have served to improve the level of performance of professionals, increase the productivity of companies, and create new challenges for the future of a society in constant technological change. In the field of education, teachers have been using technol- ogy to promote the cognitive development of their students, mak- ing the learning process more practical and attractive for them. Our study consists of analyzing fifteen articles published in the last ten years using Leximancer. This exploratory study allowed us to verify teachers’ perceptions of ICT and analyze how they have used it in the classroom and how this use facilitates/promotes student learning. The results obtained will allow us to verify the most relevant factors related to ICT and at the same time indicate the questions that will be included in a questionnaire that will be used in a second study, to be included later in the doctoral thesis underway.